Hypoglycemia-Exacerbated Mitochondrial Connexin 43 Accumulation Aggravates Cardiac Dysfunction in Diabetic Cardiomyopathy - Wei, Xing; Chang, Andrew Chia Hao; Chang, Haishuang; Xu, Shan; Xue, Yilin; Zhang, Yuanxin; Lei, Ming; Chang, Alex Chia Yu; Zhang, Qingyong (Frontiers in Cardiovascular Medicine, 2022)
Background: Diabetic cardiomyopathy (DCM) is a complex multifaceted disease responsible for elevated heart failure (HF) morbidity and mortality in patients with diabetes mellitus (DM). DCM patients exhibit subclinical diastolic dysfunction, progression towards systolic impairment, and abnormal electrophysiology. Hypoglycemia events that occur spontaneously or due to excess insulin administration threaten the lives of DM patients – with the increased risk of sudden death. However, the molecular underpinnings of this fatal disease remain to be elucidated. Methods and Results: Here we used the established streptozotocin-induced DCM murine model to investigate how hypoglycemia aggravates DCM progression. We confirmed Cx43 dissociation from cell-cell interaction and accumulation at mitochondrial inner membrane both in cardiomyocytes of patients with DM and DCM murine. Here we observed that cardiac diastolic function, induced by chronic hyperglycemia, was further aggravated upon hypoglycemia challenge. Similar contractile defects were recapitulated using neonatal mouse ventricular myocytes (NMVMs) under glucose fluctuation challenges. Using immunoprecipitation mass spectrometry, we identified and validated that hypoglycemia challenge activates the MEK/ERK and inhibits PI3K/Akt pathways which results in Cx43 phosphorylation by Src protein and translocation to mitochondria in cardiomyocytes. To determine causality, we overexpressed a mitochondrial targeting Cx43 (mtCx43) using AAV2/9. At normal blood glucose levels, mtCx43 overexpression recapitulated cardiac diastolic dysfunction as well as aberrant electrophysiology in vivo. Our findings give support for therapeutic targeting of MEK/ERK/Src and PI3K/Akt/Src pathways to prevent mtCx43-driven DCM. Conclusions: DCM presents compensatory adaptation of mild mtCx43 accumulation, yet acute hypoglycemia challenges results in further accumulation of mtCx43 through the MEK/ERK/Src and PI3K/Akt/Src pathways. We provide evidence that Cx43 mislocalization is present in DM patient hearts, STZ-induced DCM murine model, and glucose fluctuation challenged NMVMs. Mechanistically, we demonstrated that mtCx43 is responsible for inducing aberrant contraction and disrupts electrophysiology in cardiomyocytes and our results support targeting of mtCx43 in treating DCM.